Karel Martens: Printing Wor[l]ds. (4th May 2019) - Martens, Karel; Ojeda, Danné
Abstract: The text presents a conversation with Dutch designer Karel Martens held in his studio in Amsterdam, the Netherlands, in 2014. In this dialog, we focus on Karel Martens as a designer-author. We also offer an insight to specific book case studies designed by this multifaceted creator and his collaborators. Particular emphasis is given to his long lasting collaboration with the Dutch architecture magazine OASE, a publication he has engaged with since 1990. In addition, the talk also examines the particularities of printing matters before and after the digital era from a personal perspective, and how technological changes can be both a constraint and an inspiration.